Penilaian Kinerja dan Perilaku Inovatif di Era Digital - Yogananda Enggara Putra Hana (EKONOMI DAN BISNIS DIGITAL, 2023)
In the digital competitive environment, the ability of organizations to innovate more than ever is the key to competitive advantage. One way to address this increased pressure for innovation is to leverage the ability of employees to generate new ideas and use these as building blocks for new and improved products, services, and work processes. This study draws on a process-based approach to HRM (Bowen and Ostroff, 2004) suggesting that HRM practices may have a signaling effect, to answer the following research question: which specific characteristics of performance appraisal are more likely to be perceived as promoting innovation in individuals at work? To address this issue, we conducted a survey of 865 employees working in large multinational companies operating in digital sectors or industries with the potential to go digital. We collected data on the main characteristics of the performance appraisal system adopted by the company where the respondents work, as perceived by the employees themselves. We also collected data on respondents' overall perception that performance appraisal encourages innovative work behavior (IWB). Then, we employ logit analysis to examine the relationship between data on the performance appraisal system and performance appraisal effectiveness data as a driver of IWB. Our results reveal that, compared to informal feedback, formal performance appraisals are more likely to reduce the perception that performance appraisals promote individual innovation and creativity at work. In addition, we find that in employee perceptions performance appraisals that focus on achieving a predetermined quantitative outcome are more likely to influence IWB positively than assessments that focus on the predetermined skills exhibited by employees performing their jobs. However, performance appraisals focused on new competencies developed by employees have a positive perceived impact that is even stronger than results-oriented appraisals. Together, these results advance our understanding of how organizations should evaluate employees in the digital age